Al-Qaeda in Islamic Maghreb (AQIM): Terrorist Networks Infiltrate Northern Mali (Global Journal of Human-Social Science, 2014)
The Paper provides an overview of the Tuareg rebellion in Northern Mali with particular reference to conditions that are conducive to terrorist networks infiltration of the age-long insurrection in the region. In this regard, the roles played by the infiltration of Al-Qaeda in Islamic Maghreb (AQIM), the return of the Migrant workers and Tuareg combatants from Libya as well as the 22 March mutiny and Military coup in the Tuareg rebellion culminating in the total collapse of north Mali and the unilateral declaration of the independence of the State of Azawad were highlighted. Noting that the problem in Northern Mali is not that of religious extremism or terrorism and that Military answer cannot be an effective long-term strategy or solution to the recurrent rebellion in the region, the Paper indicates that the solution to the problem lies in recognizing the fact that the Tuaregs have legitimate political, socio-economic, security, environmental, humanitarian and human rights grievances that must be addressed, without which the Tuareg rebellion will continue to resonate for some time to come.